Gender-based violence and associated factors among female sex workers in Ethiopia. Evidence from The National Bio-behavioral Survey, 2020 - Debel, Lemessa; Ayalew, Jemal; Abdella, Saro; Bulti, Jaleta; Bejiga, Birra; Wariso, Fayiso Bati; Belete, Wudinesh; Habtesilase, Abebe; Lulseged, Silesh (Frontiers in Public Health, 2024)
Background Gender-based violence (GBV) is usually defined as unequal power relations between men and women, which poses a widespread public health problem. The study evaluated the prevalence and factors associated with GBV among female sex workers (FSWs) in Ethiopia. Method We used cross-sectional bio-behavioral data collected using respondent-driven sampling (RDS) in 2020 from 16 towns in Ethiopia. Descriptive statistics was analyzed to summarize the study population characteristics and prevalence of GBV, and a multilevel logistic regression model was applied to identify associated factors for GBV. A p-value of ≤0.05 was used as a threshold for statistical significance. Result Of 6,085 participants, 28.1% had experienced GBV during the last 12 months, among which 12.7% and 22.3% experienced physical and sexual violence, respectively. FSWs aged 15–24, and 25–34 than those 35 years or more, had a non-paying than paying partners, had 31–60, 61–90, and over 91 than those had less than 30 paying partners, ever had anal sex than those not, condom failure than those not, mobile female sex workers when compared with those not mobile at different town; 3–5 and ≥ 6 years than those less than 3 years stayed in selling sex, street-based, and multiple places selling sex than those used other venues were significantly associated with GBV. Conclusion Gender-based violence is a substantial problem among FSWs in Ethiopia, with significant implications for program planning on prevention and response to mitigate the occurrence and impact of GBV among FSWs.